Mid-term outcomes of moderate-severe cystocele repairing with autologous fascia lata harvested through a small incision - Bo Yu; Junfang Yang; Qingyang Nie; Kun Zhang; Jinsong Han; Yiting Wang (BMC Surgery)
Abstract Introduction and hypothesis To investigate the mid-term outcomes of transvaginal repair for moderate-severe cystocele using autologous fascia lata harvested through a single small incision. Methods Between February and October 2022, 35 patients with moderate to severe cystocele undergoing transvaginal repair with autologous fascia lata were included. Patient demographics and perioperative data were collected, with follow-ups through outpatient visits or phone calls. Patients were evaluated by subjective perception of vaginal bulging, physical examination, Pelvic Floor Distress Inventory (PFDI-20) Questionnaire, patient satisfaction, Patient Global Impression of Improvement (PGI-I) scores, regret rate, willingness to recommend, complications, and harvesting site issue. Results The patient’s mean age was 60.44 ± 6.01 years. Fascia lata harvesting took 32.92 ± 19.72 min, reconstruction surgery lasted 141.21 ± 37.89 min. Follow-up duration was 15.94 ± 2.46 months. 5.7% (2/35) of the patients reported a non-interfering vaginal bulge not requiring treatment. Objective recurrence rate was 4.26% (1/24, Aa or Ba>0) PFDI-20 was significantly improved (P < 0.0001). All 35 patients (100%) were highly satisfied, with PGI-I score very much improved or improved. No patient regretted. 97.14% (34/35) would recommend the procedure. One patient developed poor wound healing at the vaginal apex. One patient developed thromboembolic event. Harvest site: 2.86% (1/35) developed a non-bothersome thigh bulge, 17.14% (6/35) noted an impact on wound appearance, and 8.57% (3/35) reported mild paresthesia. Conclusion Autologous fascia lata for cystocele treatment shows promising mid-term outcomes, safely and effectively enhancing QoL with high satisfaction. Despite concerns about leg scarring, no patient regretted and would recommend the procedure. Long-term outcomes require larger follow-up studies.